FATWA ABOUT SOCIAL INTERACTION ON SOCIAL MEDIA IN THE PARADIGM OF ISLAMIC LEGAL PHILOSOPHY - Islamy, Athoillah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 15 No 2 (2019)DO - 10.24239/al-mishbah.Vol15.Iss2.159, 2020)
This study aims to find the paradigm of Islamic legal philosophy contained in the Fatwa of the Indonesian Ulema Council (MUI) regarding guidelines for social interaction through social media. This type of research is qualitative research (library research). Data sources of this study is the Fatwa of MUI, No.24 of 2017 Concerning Law and Guidelines for Bermuamalah through Social Media and various relevant literature. The theory used in this research is the Maqasid Shariah theory. This study concludes that the Fatwa of MUI legal provisions that limit freedom of social interaction through social media are legal provisions in realizing the benefit of individuals (al-maslahat al-khassah) and the public (al-maslahat al-ammah) in the context of social life. To realize these two benefits, the five objectives of Islamic law (maqasid shari'ah al-khomsah), such as hifz al-nafs, hifz al-aql, hifz al-mal, hifz al-nasl can be manifested in various legal provisions of the fatwa of MUI which limits freedom of social interaction on social media.